Bros [videorecording (Blu-Ray + DVD)] - Stoller, Nicholas; Eichner, Billy, 1978-; Eichner, Billy, 1978-; MacFarlane, Luke; Chenoweth, Kristin; Messing, Debra, 1968-; Raymund, Monica, 1986- (Universal Studios, 2022)
Bobby is a struggling podcast host who hates commitment. That all changes when he meets Aaron, a detached lawyer who likes to play the field. Repeatedly drawn to each other, both men begin to show their vulnerable sides as their undeniable attraction turns into something resembling a commitment.